Family-Centred Care in Paediatric and Neonatal Nursing- A Literature Review - L.K. Irlam; J.C. Bruce (AOSIS, 2002)
A literature review of family-centred care in paediatric and neonatal nursing was undertaken as part of a research project. This research intended to ascertain the knowledge and attitudes of paediatric and neonatal qualified nurses and nurse educators towards family-centred care as it pertains to infants and children in hospitals in the Gauteng Province. A definition of family-centred care is difficult to formulate mainly due to the lack of consensus about its meaning. Additionally, the diverse societal contexts within which family-centred care is applied further complicate its definition. Internationally in developed countries, family-centred care is viewed as care, which is parent-led in consultation with the nurse practitioner. A family-centred care model for the South African context needs to be developed with the focus on parent participation, a precursor of family-centred care. This article traces the early developments in parental care for hospitalised children with specific reference to the USA, the UK and South Africa. Precursor concepts in family-centred care are described followed by a cursory overview of the reality of family-centred care, its cultural dimensions and matters of family strengths and choices in family-centred care.